The evolution of raw material procurement strategies: A view from the deep sequence of Tabun Cave, Israel. Issue 143 (June 2020) - Shimelmitz, Ron; Kuhn, Steven L.; Weinstein-Evron, Mina
Abstract: Changes in the ways Paleolithic foragers exploited raw material sources are linked to mobility, the demands of production, and investment in quarrying. Here, we analyze the use of raw materials in a long series of superimposed layers from Tabun Cave dating to the Middle Pleistocene, attributed to the Lower and Middle Paleolithic periods. Using the cortex preserved on the surfaces of artifacts, including blanks, tools and cores, we distinguished between flints obtained from primary and secondary geological contexts. The results from Tabun Cave indicate that the exploitation of secondary sources was fairly common during the earlier part of the Lower Paleolithic sequence. It decreased during the later part of the Acheulo-Yabrudian complex of the Lower Paleolithic, coinciding with growing use of predetermined technological strategies, which demand high-quality raw materials. By the Middle Paleolithic, primary and secondary raw materials are generally designated for different reduction trajectories, suggesting a growing distinction and formalization of technological strategies. The need for the 'best' stone for Middle Paleolithic laminar and Levallois production may have necessitated increased investment in raw material procurement. During most of the Lower Paleolithic, raw material needs could have been met easily through a purely embedded strategy, in which raw material was collected while focusing on other activities. Starting in the late Acheulo-Yabrudian and especially during the Middle Paleolithic, the focus on primary geological contexts may have demanded greater planning of visits to raw material outcrops. In other words, in the Middle Paleolithic and possibly already during the very end of the Lower Paleolithic, raw material procurement had greater influence on patterns of movement through the landscape.